A Comparative Study of the Regulation of Liability for Criminal Acts of Child Bullying Perpetrators Causing the Victim's Death According to Islamic Criminal Law and Positive Criminal Law in Indonesia - Rahmatika. HB, Ghina; Rinda Listyawati, Peni (Jurnal Hukum Khaira Ummah, 2025)
Bullying is a form of violence that causes serious physical and psychological effects and has become a global problem, including in Indonesia. Although often considered trivial, bullying often has traumatic effects and can even cause the death of victims, as in the case in South Kalimantan. The contributing factors include economic differences, gender, seniority, and the perpetrator's desire for social influence. Legally, child perpetrators receive special treatment under the Child Protection Act and the Child Criminal Justice System Act (UU SPPA), which emphasizes restorative justice and diversion. However, in cases resulting in death, there is a dilemma between the need for justice for the victim and protection for the perpetrator, who is still a child. In Islamic criminal law, bullying is classified as a crime and may be subject to qisas punishment if it causes death, or ta'zir if it causes injury or psychological trauma. However, children who have not reached puberty are not subject to qisas punishment, but rather rehabilitation, and responsibility can be transferred to a guardian. The objectives of this study are: 1) to determine how the criminal responsibility of child perpetrators of bullying that results in the death of the victim is regulated under Islamic criminal law; 2) To determine how the criminal responsibility of children who commit bullying that results in the death of the victim is regulated in the perspective of positive criminal law in Indonesia, 3) To determine the similarities and differences regarding the regulation of criminal responsibility for children who commit bullying that results in the death of the victim between Islamic criminal law and positive criminal law in Indonesia. The research method used in this study is normative legal research, with a descriptive-comparative research specification. The data collection method used is library research, while the data analysis method used in this study is descriptive analysis. The research results show that the criminal liability of children who commit bullying that results in the death of the victim according to Islamic law is that children who have not reached puberty are not subject to severe criminal punishment but may be subject to ta'zir sanctions to educate and prevent repetition of the act. Liability is also transferred civilly to the child's guardian in the form of diyat payment to the victim's family. According to positive criminal law in Indonesia, actions by children that result in the victim's death are still being processed legally, but with a proportional and educational approach. There are fundamental similarities and differences. Both agree that children cannot be treated like adults and prioritize the protection, education, and guidance of children through a restorative and educational approach. However, there are similarities and differences. Both agree that children cannot be treated like adults and prioritize the protection, education, and guidance of children through a restorative and educational approach. However, there are differences in the age of criminal responsibility, types of punishment, case handling systems, and legal sources. Islamic law emphasizes maturity based on puberty and recognises diyat as a form of accountability, while positive law uses an age limit of 12–18 years and does not recognize diyat, but rather criminal penalties or corrective measures.